Masculino de 38 años con diagnóstico reciente de infección por VIH y tuberculosis pulmonar, inició terapia antifímca y antiretroviral con posterior deterioro clínico y hemodinámico. En la autopsia se documentó tuberculosis y Kaposi diseminados. - Monge, Ixchel Flores (2019)
We present the case of a 38-year-old male patient, homeless, drug-dependent condition, with no known medical history; whom, due to weight loss, hematemesis and bloody diarrhea studios, was diagnosed with acquired immunodeficiency syndrome with infection due to pulmonary tuberculosis; antimycobacterial therapy was started. After 15 days of initiation of antituberculosis therapy, antiretroviral therapy was initiated. The picture evolved with hemodynamic deterioration and the patient died. The autopsy showed findings compatible with disseminated tuberculosis.